Lipoprotein markers associated with disability from multiple sclerosis. Issue 1 (December 2018) - Gafson, A.; Thorne, T.; McKechnie, C.; Jimenez, B.; Nicholas, R.; Matthews, P.
Abstract Altered lipid metabolism is a feature of chronic inflammatory disorders. Increased plasma lipids and lipoproteins have been associated with multiple sclerosis (MS) disease activity. Our objective was to characterise the specific lipids and associated plasma lipoproteins increased in MS and to test for an association with disability. Plasma samples were collected from 27 RRMS patients (median EDSS, 1.5, range 1–7) and 31 healthy controls. Concentrations of lipids within lipoprotein sub-classes were determined from NMR spectra. Plasma cytokines were measured using the MesoScale Discovery V-PLEX kit. Associations were tested using multivariate linear regression. Differences between the patient and volunteer groups were found for lipids within VLDL and HDL lipoprotein sub-fractions (p < 0.05). Multivariate regression demonstrated a high correlation between lipids within VLDL sub-classes and the Expanded Disability Status Scale (EDSS) (p < 0.05). An optimal model for EDSS included free cholesterol carried by VLDL-2, gender and age (R2  = 0.38, p < 0.05). Free cholesterol carried by VLDL-2 was highly correlated with plasma cytokines CCL-17 and IL-7 (R2  = 0.78, p < 0.0001). These results highlight relationships between disability, inflammatory responses and systemic lipid metabolism in RRMS. Altered lipid metabolism with systemic inflammation may contribute to immune activation.